Effect of aspirin discontinuation according to individualised patient bleeding and ischemic risks after PCI: a TWILIGHT trial sub-analysis. (3rd October 2022) - Mendieta Badimon, G; Mehta, S; Baber, U; Collier, T; Dangas, G; Sharma, S K; Cohen, D J; Angiolillo, D; Briguori, C; Escaned, J; Gabriel Steg, P; Huber, K; et al.
Abstract: Background: The TWILIGHT trial demonstrated a reduction in BARC 2, 3 or 5 (BARC-235) bleeding without an increase in ischemic events at 1-year in high-risk PCI patients randomized to placebo or aspirin (ASA) on a background of ticagrelor 3-months after PCI. However, the effect of ASA discontinuation according to baseline risk of bleeding and ischemic events remain unclear. Purpose: To a) develop separate models to predict the risk of bleeding and ischemic events, and b) to assess treatment effect of ASA discontinuation across the risk strata. Methods: Using the TWILIGHT patient database (N=7, 119), two multivariable models, one for BARC-235 bleeding and one for CV death, nonfatal MI or nonfatal ischemic stroke (ischemic endpoint) were developed, and their predictive capacity was assessed. The effect of randomized treatment on bleeding and ischemic events across different patient risk-group categories as determined by the risk scores was investigated. Results: At 1-year, 350 (5.4%) patients experienced a BARC-235 bleeding event and 258 (3.6%) experienced an ischemic event. Independent predictors of BARC-235 included haemoglobin levels at index PCI, proton-pump inhibitor non-use at discharge, age, liver disease and active smoking (c-statistic 0.64). Independent predictors of the ischemic outcome included a positive troponin ACS, prior CABG, diabetes, age, peripheral artery disease, prior PCI, a history of congestive heart failure, active smoking, the level of index PCI complexity, and prior MI (c-statistic 0.71). The risk of a BARC-235 almost doubled between patients in lower versus higher bleeding risk categories (4.3% versus 7.9%) and ischemic risk more than tripled between patients in lower versus higher ischemic risk categories (2.0% versus 7.0%) (see Figure 1). There was no evidence of a differential treatment effect for dual antiplatelet therapy versus ticagrelor monotherapy across the different risk categories of bleeding (interaction P=0.54) and ischemic risk (interaction P=0.95) (Table 1). Conclusion: Individual patient bleeding and ischemic risks after PCI can both be readily characterised with good discrimination. The effect of ASA discontinuation in preventing bleeding in ticagrelor-treated patients was consistent regardless of baseline bleeding risk. There was no evidence for increased ischemic events with ASA discontinuation according to baseline ischemic risk. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): AstraZenecaIcahn School of Medicine at Mount Sinai